Management of the Energy Mix and Emissivity of Individual Economies in the European Union as a Challenge of the Modern World Climate - Miciuła, Ireneusz; Wojtaszek, Henryk; Bazan, Marek; Janiczek, Tomasz; Włodarczyk, Bogdan; Kabus, Judyta; Kana, Radomir (Energies (Basel), 2020)
The aim of the article is to present the most important elements to be implemented in the European Union energy policy in the 2030 perspective in the context of sustainable development of the Member States. The solution to the too high emissivity of individual economies in the European Union is the energy mix, which will establish a compromise in the so-called the triad of EU policy goals. This is undoubtedly a current climate challenge for the modern world, which also has a direct impact on the economic situation of EU countries. The basis of the presented considerations and recommendations is a literature review on the subject and a statistical analysis of empirical data of the largest statistical organizations in the EU and the world. The starting point for the analysis is the assessment of the state of the energy sector in the EU. Therefore, the goals and tasks until 2030 result from many conditions of the energy sector. The article provides recommendations for the EU on future climate and energy policy, analysing the practices of member countries empirical and data compiled by the world’s largest organizations and institutions, such as the International Atomic Energy Agency (IAEA), the World Nuclear Association (WNA), Eurostat, and the International Energy Agency (IEA). The strategic goals of the EU climate and energy policy presented in the study show the necessary challenges for the implementation of sustainable development in the analyzed sector, which is the driving force of world economies. The conclusions were presented in accordance with the current economic efficiency of various energy sources and the necessity to seek a compromise among the so-called a triad of goals defined in EU policy.